PEMBELAJARAN SINTAKSIS BAGI PEMBELAJAR ASING YANG BERBAHASA PERTAMA BAHASA INGGRIS - Latifah Latifah (STKIP Siliwangi, 2013)
Syntax is a branch of linguistics that discuss the relationship between words in speech , language elements that are included in the scope of syntax is a phrase, clause , sentence . Learn syntax for foreign speakers is not easy , it takes a lot of practice so that students are able to understand the material and found it difficult syntax of the results of the exercises . Difficulties and constraints Indonesian Phrases patterned material or noun - adjective DM , whereas the English phrase patterned MD - noun or adjective , thus allowing the formation of fault Indonesian phrases by foreign speakers . Difficulties in material clauses are any deformities of grammatical tense marker in English into lexical time markers in Indonesian . The existence of multiple forms of predicates in the English language into a form of predicate in Indonesian can actually facilitate foreign learners in learning Indonesian clause for foreign learners do not need to be bothered with the selection predicate forms that must be used . Learning difficulties at the level of sentences for foreign speakers closely associated with a lack of understanding of the concept of morphological. By understanding the difficulties experienced by the learners experienced difficulties in practice able to be overcome by focusing on the difficulties faced by learners.Keywords :syntactic learning for foreign speakers